1976
DOI: 10.1007/bf00425096
|View full text |Cite
|
Sign up to set email alerts
|

Hyphal wall chemistry in Apodachlya

Abstract: Hyphal walls were isolated from the Oomycete, Apodachlya sp. Microscope examination of wall preparations showed that they were clean and relatively free of cellulin granules. The principal wall constituents, accounting for more than half of wall weight, were beta-glucans with 1,3- and 1,6-glucosidic linkages. Apparently chitin was the second most abundant wall constituent (18%) and cellulose accounted for less than 10% of wall weight. Protein was a significant wall constituent (6.4%), and protein hydrolysis de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

1980
1980
2008
2008

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(7 citation statements)
references
References 24 publications
0
7
0
Order By: Relevance
“…More recently, WGA labeling has also confirmed biochemical evidence (Lin et al, 1976;Campos-Takaki et al, 1982;Bulone et al, 1992) of the presence of a small amount of chitin in the predominantly cellulosic walls of members of the Oomycetes (Burr and Beakes, 1994;Asiegbu et al, 1996). The functional significance of this small chitin fraction remains to be determined, but knowledge of its presence is important for studies of the plant response to Oomycete pathogens.…”
Section: Fungal Cell Structure and Functionmentioning
confidence: 75%
“…More recently, WGA labeling has also confirmed biochemical evidence (Lin et al, 1976;Campos-Takaki et al, 1982;Bulone et al, 1992) of the presence of a small amount of chitin in the predominantly cellulosic walls of members of the Oomycetes (Burr and Beakes, 1994;Asiegbu et al, 1996). The functional significance of this small chitin fraction remains to be determined, but knowledge of its presence is important for studies of the plant response to Oomycete pathogens.…”
Section: Fungal Cell Structure and Functionmentioning
confidence: 75%
“…However, some exceptions in fungi are known. The oomycete Apodachlya is reported to have chitin as well as cellulose in its cell walls (Lin et al, 1976). In taxa above node D ( Fig.…”
Section: S E Xmentioning
confidence: 99%
“…Apodaahlya sp. and A. bvaahynema walls differ from those of Sapromyaes in having glucosamine (Sietsma et al 1969;Lin et al 1976). X-ray diffraction studies and stains for chitin indicated the presence of both weakly crystalline cellulose I and chitin in these walls (Lin and Aronson 1970 braahynema contain phospholipids, fatty acids, and triglycerides (Sietsma et al 1969).…”
Section: Ascomycete Wallsmentioning
confidence: 99%
“…cellulose, 6.4% protein, 1.5% acid-soluble hexosamine, and 3.1% alkalisoluble hexosamine (Lin and Aronson 1970;Lin et al 1976). Analysis of the hyphal wall chemistry of Leptomitus laateus indicated similarity to the walls of Sapromyces and Apodaahlya, especially in regard to the linkage pattern (Aronson and Lin 1978) .…”
Section: Ascomycete Wallsmentioning
confidence: 99%
See 1 more Smart Citation